(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article examines the theoretical and practical dimensions of the competency-based approach in developing technical thinking in economics education. It scientifically explores the role of modern digital technologies, project-based learning, case-study methodology, and problem-based instruction in fostering students’ analytical thinking, algorithmic reasoning, economic process modeling, and technical problem-solving skills. Furthermore, advanced international practices in cultivating technical thinking through a competency-based framework are reviewed, and recommendations for their effective implementation in the context of Uzbekistan are proposed.